(untitled) (Management Dynamics, 2024)
The study focuses on career development and task performance among faculty members in higher educational institutions in Nepal, primarily examining the factors influencing career development and its effect on the task performance of university teachers. The study aims to investigate the status and impact of career development on the task performance of these educators. To achieve this, a descriptive and explanatory research design was used. Data were collected from permanent faculty members at selected campuses using a stratified sampling technique and a structured Google Form questionnaire. Out of 1,216 distributed questionnaires, 406 valid responses were obtained and analyzed. Empirical analysis was conducted using SPSS, with descriptive statistics calculated through the mean and standard deviation. The impact was assessed using multiple regression analysis tools. The findings revealed that participation in a professional community, effective practice implementation, innovative knowledge sharing, and high performance among colleagues significantly and positively influence task performance. However, feedback from the department did not show a significant impact on task performance. This study is expected to provide valuable insights for academic institutions to identify critical workplace issues, develop strategies to address them, and enhance the quality of task performance.